Controlled Pd deposition on fibers by electroless plating. The effects of the support on the reduction of nitrite in water - Bosko, María Laura (2013)
Pd catalysts supported on activated silica?alumina fibers (CFs) and activated carbon felts (ACFs) were prepared and evaluated for the reduction of nitrite in water in a batch reactor. The electroless plating (ELP) method was used in order to deposit small Pd particles on the surface of the fibers. While a homogeneous distribution of Pd nanoparticles was obtained for carbon fibers, this was not the case for ceramic onesin which non-homogeneous patches of Pd films were formed. This fact resulted in a higher activity fornitrite reduction when carbon fibers were used. However, the selectivity toward the undesired productammonia, measured at the end of the reaction, was slightly higher for Pd/ACFs catalysts.